P–287 Uterine adenomyosis does not affect perinatal outcomes in ART treatments. (6th August 2021) - Trinchant, R; Cruz, M; Requena, A
Abstract: Study question: Is adenomyosis associated with worse clinical and perinatal outcomes in ovum donation cycles? Summary answer: Adenomyosis was associated with reduced live birth rate per embryo transfer but not with increased risk of miscarriage or worse perinatal outcomes than controls. What is known already: The effect of adenomyosis on IVF/ICSI outcomes are controversial as studies addressing this issue are limited in number and heterogeneous. Conclusions withdrawn from previous works differ regarding the prospective or retrospective design of the study. Two different metanalysis conducted showed that adenomyosis reduced implantation and clinical pregnancy rate and increased miscarriage risk. However, current data regarding perinatal outcomes of assisted reproduction techniques cycles in patients diagnosed with uterine adenomyosis is scarce. Study design, size, duration: A retrospective cohort study in which 3307 patients undergoing ovum donation cycles were included. Patients who underwent single embryo transfer (SET) between years 2018 and 2019 were included and divided into two groups: adenomyosis (n = 179) and controls (n = 3218). Participants/materials, setting, methods: Inclusion criteria consisted of patients in an oocyte donation program who had fresh SET on day 5 blastocyst stage development. Patients diagnosed with miomas and/or severe endometriosis and those who had undergone previous uterine surgical interventions were excluded from the study. Cases consisted of patients with a history of either focal or diffuse adenomyosis diagnosed via transvaginal ultrasonography (TVUS). Main results and the role of chance: Clinical pregnancy rate per embryo transfer was 82/179 (45.8%) in those women diagnosed with adenomyosis versus 1869/3218 (59.8%) in control group (OR = 0.57 95% CI. 0.41–0.78, p < 0.001). Miscarriage rate was similar in the two study groups and differences found were not statistically significant, being 15/82 (18.3%) for adenomyosis and 309/1869 (16.5%) for control group. A lower live birth rate per embryo transfer was observed in women diagnosed with adenomyosis versus control, being 68/179 (38%) and 1560/3128 (49.9%) respectively (OR = 0.615 95% CI 0.44–0.85, p = 0.002). There were no statistically significant differences between childbirth delivery methods (vaginal versus caesarean section). Furthermore, means of gestational age at the time of delivery, newborn size and weight and incidences of low birth weight, preterm birth and admission in neonate intensive care unit (NICU) did not differ between the two groups. In addition, IVF and perinatal outcomes were similar in patients with diffuse adenomyosis compared to focal adenomyosis. Limitations, reasons for caution: This is an observational study and thus possible confounders cannot be completely excluded. Diagnostic of adenomyosis is complex and, despite imaging via TVUS is both sensitive and specific, different criteria may be combined in order to fully assess the diagnostic. Wider implications of the findings: Published literature has described how adenomyosis negatively impacts clinical outcomes in ART cycles; however, data regarding perinatal results is scarce. This study is of interest as it provides a first insight for clinicians showing that adenomyosis affects clinical but not perinatal outcomes in ovum donation cycle. Trial registration number: Not applicable